Opportunities and challenges in preserving and revitalizing the Tibetan oral literature Shépa in Chone. Issue 1 (1st August 2019) - Tso, Bendi
This article explores the ongoing Shépa preservation and revitalization in Chone County of Kanlho Tibetan Autonomous Prefecture, China. Shépa is an expansive collection of Tibetan cultural wisdom composed as oral poetry and performed in antiphonal style in Chone. It captures the most salient aspects of Chone Tibetan cultural identity and linguistic practices. Yet, along with the erosion of the Chone Tibetan language, the inter-generational transmission of Shépa has been seriously interrupted. Given this picture, since 2016, various efforts have been made by the stakeholders (local community members, Shépa narrators, language and cultural activists, and Chone County Government) to preserve and revitalize Shépa. These efforts include but are not limited to the transcription and teaching of Shépa through Chinese, the establishment of Chone Shépa Cultural Association in 2017, the government-funded Shépa performance both within and outside Chone County and so forth.Through using qualitative research methods, including participant observation and semi-structured interviews with all stakeholders, this article first documents the processes of how Chone Tibetans reclaim and revitalize their oral tradition, Shépa. It also examines the tensions derived from the processes and explores how local communities negotiate and manage these challenges. The research results will contribute to the conversation on the importance and complexities of oral tradition preservation in Indigenous communities in Tibet and beyond.